Digital Populism: An Analysis of Donald Trump’s Rhetoric in X - Hoimawati Talukdar; Medusmita Borthakur; Ismojo Herdono (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study examines the political discourse of Donald Trump on X during his return to office (2024–2025), with a focus on how his tweets construct polarized narratives across major geopolitical conflicts, including Russia–Ukraine, Israel–Palestine, Iran–Israel, the Houthis, India–Pakistan, and U.S. domestic politics. The primary objective is to analyze how Trump reproduces the